A High-Throughput Size Exclusion Chromatography Method to Determine the Molecular Size Distribution of Meningococcal Polysaccharide Vaccine - Imran Khan; K. M. Taufiqur Rahman; S. M. Saad Us Siraj; Mahbubul Karim; Abdul Muktadir; Arpan Maheshwari; Md Azizul Kabir; Zebun Nahar; Mohammad Mainul Ahasan (International Journal of Analytical Chemistry)
Molecular size distribution of meningococcal polysaccharide vaccine is a readily identifiable parameter that directly correlates with the immunogenicity. In this paper, we report a size exclusion chromatography method to determine the molecular size distribution and distribution coefficient value of meningococcal polysaccharide serogroups A, C, W, and Y in meningococcal polysaccharide (ACWY) vaccines. The analyses were performed on a XK16/70 column packed with sepharose CL-4B with six different batches of Ingovax® ACWY, a meningococcal polysaccharide vaccine produced by Incepta Vaccine Ltd., Bangladesh. A quantitative rocket immunoelectrophoresis assay was employed to determine the polysaccharide contents of each serogroup. The calculated distribution coefficient values of serogroups A, C, W, and Y were found to be 0.26±0.16, 0.21±0.11, 0.21±0.11, and 0.14±0.12, respectively, and met the requirements of British Pharmacopeia. The method was proved to be robust for determining the distribution coefficient values which is an obligatory requirement for vaccine lot release.